Women's role in food security in Tunisia - Mellouli K. (Mainstreaming gender dimensions in water management for food security and food safety, 2007)
This paper reports the efforts made by the State for social promotion through social assistance and the programme to combat poverty, preventing conflicts and creating a peaceful environment. The paper describes, in particular, how rural women contribute to food security. An effort was made to strengthen gender equality and women empowerment. Despite such efforts, the State has difficulties in distinguishing the role of the rural women in food security through their role in agriculture.
2. Regional Coordination Workshop of GEWAMED (Mainstreaming Gender Dimensions into Water Resources Development and Management in the Mediterranean Region), 2007/03/12-14, Larnaca (Cyprus)